An evaluation of echography in the diagnosis of pancreatic disease. Issue 3 (March 1976) - Fontana, G; Bolondi, L; Conti, M; Plicchi, G; Gullo, L; Caletti, G C; Labo, G
Abstract : In the present study an attempt to evaluate the efficacy of echography as a diagnostic tool has been made. A total of 52 patients (chronic pancreatitis (42); pancreatic cysts (three); and carcinoma of the pancreas (seven)) were studied and the results compared with those from other diagnostic techniques. In 65.7% of chronic pancreatitis patients, and in all cases of carcinoma of the pancreas, echography provided evidence of pancreatic abnormality but in no case could an unambiguous diagnosis of the disease be made. However, in all cases of pancreatic cyst, echography gave precise and unequivocal diagnostic information. There was good agreement between the echographic picture and surgical findings. Cholangiography and duodenography indicated duodenal and choledochal compression in a high proportion of cases in which echography revealed enlargement of the head of the pancreas. It is concluded that echography is a simple, safe, and valuable addition to the techniques available for studying the pancreas.